Gender Differences in the Relationship Between Exercise, Sleep, and Mood in Young Adults. (February 2022) - Glavin, Emily E.; Matthew, Juliet; Spaeth, Andrea M.
Insufficient sleep is a serious public health problem in college students. Exercise is a widely prescribed behavioral treatment for sleep and mood issues; however, more focused and gender-specific prescriptions are needed. The present study examined relationships between exercise, sleep, and mood in undergraduate men and women. Students ( N = 866, 19.6 ± 1.4 years, 38.7% women) were recruited from campus recreation facilities and completed demographic, the Pittsburgh Sleep Quality Index, mood (Patient-Reported Outcomes Measurement Information System), and exercise questionnaires. The Department of Health and Human Services Physical Activity Guidelines were used to dichotomize those who did and did not meet weekly aerobic and strength training exercise recommendations. In men, greater exercise frequency associated with less daytime dysfunction (β = 0.147) and less depressive mood (β = −0.64, p s < .05). In women, greater exercise frequency associated with earlier bedtime (β = −12.6), improved sleep quality (β = 0.17), increased positive affect (β = 0.91), less depressive mood (β = −0.71), and less anger (β = −1.24, p s < .05). Compared to men, women reported earlier bedtime, poorer sleep efficiency, and more anxiety and depressive mood ( p s < .05, η p 2 range: 0.01–0.04 ). Compared to individuals who met physical activity guidelines, those who did not meet the guidelines reported later bedtimes, less positive affect, more anxiety, and more anger ( p s < .05η p 2 s = 0.01). Among men, those who met physical activity guidelines reported falling asleep more quickly than those who did not meet guidelines (η p 2 = 0.01, p = .007); however, no relationship between guideline adherence and sleep latency was observed in women. Adhering to physical activity guidelines may be important for optimal sleep and emotional health. Clinicians should consider gender when creating exercise prescriptions for sleep issues.